Short Messaging Service (SMS) adoption among people with visual impaired in Malaysia / Mohd Aidil Riduan Awang Kader ...[et al.] - Awang Kader, Mohd Aidil Riduan; Mohezar Ali, Suhana; Ali, Roslina; Mat Yunus, Nor Khairunnisa; Mohamed Badri, Shamsul Nizam (2013)
Nowadays, Short Messaging Service (SMS) adoption among communities is common and has been used extensively as one of the medium of communication and message delivery. This technology has been used not only among normal people but also it has been used by people who have visual impaired This means the growth of technology not just limited to the normal users but it is also can give benefit to the people who have visual impaired by helping them learn to live more independently. The objectives of this research are to determine significant factors influencing the adoption of SMS among people with visual impaired and to investigate the SMS adoption as a main mechanism for sending messages among them. The study successfully revealed that the two dimensions, namely usefulness and ease of use do have positive relationship with user's behavioral intention of SMS. Usefulness appeared to be the strongest determinant for behavioral intention, followed by ease of use. However, there was lack of support for enjoyment and perceived fees on SMS adoption among people with visual impairment. The benefits such as ease of use should not be neglected in the development of new functions and enhancement of service features especially for visual impaired community. It also may give an important consideration when developing pricing policies and marketing strategies for more innovative and value-added SMS particularly for visual impaired community.